Vanishing legal justice : the changing role of judges in an era of settlements and plea bargains / Michal Alberstein, Nofit Amir. - Alberstein, Michal; Amir, Nofit (Cambridge University Press, 2025)
A full trial has become an uncommon phenomenon in many legal systems, replaced largely by promotion of settlement and plea-bargaining. This book uncovers today's judicial role in this radically changed legal setting using multiple methods. Over five years, researchers analyzed court dockets, studied judges in action, and conducted interviews with judges and lawyers. This book, which spans several legal cultures, follows in the footsteps of the 'vanishing trial phenomenon', probing its existence beyond common law systems. In doing so, it provides insights into the changing judicial role and the metamorphosis of legal systems. Offering a new perspective on possible futures of legal systems, including the use of artificial intelligence, the authors provide a rich context for legal scholars and policymakers to redesign the architecture of conflicts. Moreover, they introduce new jurisprudential perspectives on the relationship between law and conflict resolution, with an emphasis on the judicial role.